Giant Angioleiomyoma of Knee Presenting as Painless Ulcer: The First Case Report - Gupta, Souradip (Indian J Dermatol, 2015)
Angioleiomyomas are benign tumors originating in the vascular smooth muscle. The tumor typically presents as painful, solitary, small (<2 cm), slow growing, subcutaneous nodule. Angioleiomyoma of the knee is rare, and only few cases have been reported so far. We have described herein a giant angioleiomyoma of the knee presenting as a painless ulcer in a 22-year-old man. There was no intra-articular extension of the tumor, and total excision was curative. This is the first case report of giant angioleiomyoma of the knee as well as the first case report of angioleiomyoma presenting as a painless ulcerative lesion.